Correlation of Objective Assessment of Facial Nerve Paralysis with House-Brackmann (HB) Score - Wan Syahirah, Wan Samsudin; Rosdiyana, Samad; Kenneth, Sundaraj; Mahfuzah, Mustafa; Nor Rul Hasma, Abdullah (2016)
This article illustrated a brief review of some objective methods in assessing facial nerve function for facial nerve paralysis which are correlated with House-Brackmann Grading System (HBGS). A rigorous search of online databases such as Springer, Elsevier, IEEE, ACM digital library, PubMed, and Wiley online library was conducted from June, 2015 to November, 2016 to discover and analyze the previous works in facial nerve assessment methods for facial paralysis. A brief introduction of facial nerve and the paralysis condition is provided. Several domains (facial muscle, type of facial disorder, facial grading system and methods used to evaluate the facial nerve function) were extracted for further analysis. Different keywords were used to acquire the studies based on the desire criteria. A total of 8 articles were identified and were analyzed for inclusion in this search. A brief presentation on each method is provided. In conclusion, this review has presented an initial overview for further improvements in objective facial nerve assessment which has to be correlated with subjective assessment to make it more reliable and useful in clinical practice.